Using rich models of language in grammatical error detection - Da Costa, Luis Morgado (Nanyang Technological University, 2022)
In this thesis, I show the advantages of using symbolic parsers for Grammatical Error Detection and Correction. In particular, I work with computational grammars for English and Mandarin Chinese to demonstrate how linguistically motivated research using symbolic parsers is still an extremely viable approach to build educational applications.